2016
DOI: 10.7567/apex.9.094101
|View full text |Cite
|
Sign up to set email alerts
|

Amplified spontaneous emission of phonons as a likely mechanism for density-dependent velocity saturation in GaN transistors

Abstract: We show that density-dependent velocity saturation in a GaN High Electron Mobility Transistor (HEMT) can be related to the stimulated emission of longitudinal optical (LO) phonons. As the drift velocity of electrons increases, the drift of the Fermi distribution in reciprocal space produces population inversion and gain for the LO phonons. Once this gain reaches a threshold value, the avalanche-like increase of LO emission causes a rapid loss of electron energy and momentum and leads to drift velocity saturati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…A pure mechanical phonon laser operating at 100 kHz has also been achieved recently using a piezoelectric excitation of a micromechanical resonator ( 40 ). Much higher frequencies, achieved using optical phonons of solids, have also been considered ( 41 , 42 ). However, as was pointed out by Chen and Khurgin ( 41 ), the very large optical phonon density of states makes the realization of these optical phonon lasers difficult as all the modes of the resonator within the energy range of the gain must be populated until the threshold is reached for the mode with the large gain and lower losses.…”
Section: Discussionmentioning
confidence: 99%
“…A pure mechanical phonon laser operating at 100 kHz has also been achieved recently using a piezoelectric excitation of a micromechanical resonator ( 40 ). Much higher frequencies, achieved using optical phonons of solids, have also been considered ( 41 , 42 ). However, as was pointed out by Chen and Khurgin ( 41 ), the very large optical phonon density of states makes the realization of these optical phonon lasers difficult as all the modes of the resonator within the energy range of the gain must be populated until the threshold is reached for the mode with the large gain and lower losses.…”
Section: Discussionmentioning
confidence: 99%
“…Transconductance (g m ) drop-off at larger gate bias & nonlinear resistance of source are the major sources for nonlinear device behavior. [38][39][40] Transconductance drop-off mainly because of decreased saturation velocity of carrier with increased carrier density at high V GS . The InGaN/GaN channel layer enables almost a constant charge density of electrons in the channel due to the polarization charge gradient.…”
Section: Resultsmentioning
confidence: 99%
“…The non-linear source resistance and density-dependence velocity saturation are the major reason for the G M drop-off. 24,25 Therefore, improvement in linearity of the device to be considered and there have been very few research groups are investigated and reported on linearity improvement of InAlN barrier based III-nitride HEMTs.…”
Section: Introductionmentioning
confidence: 99%